Peer Group Tari Tradisional dalam Mencegah Gangguan Gerak Tubuh Orang dengan Gangguan Jiwa - Alfianto, Ahmad Guntur; Ulfa, Miftakhul; Kurniyanti, Mizam Ari; Sulaksono, Ari Dwi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Stigma and movement disorders due to drugs in people with mental disorders create problems in the community. Efforts that can be made to prevent through preventive efforts are empowerment in the community. Peer groups are a form of empowerment between peer groups. The aim of this program is to train youth groups in helping ODGJ reduce movement disorders caused by mental disorders drugs. The method used is through FGD and measuring partners' knowledge and dancing skills. The program will be implemented in June 2023. The stages include pre-program, module prescription testing, program socialization, traditional dance peer group training, and evaluation and follow-up plans. The pre-program results agreed regarding advocacy activities for people with mental disorders, the results of the perception equality test (ICC: 0.945), the knowledge value of (p= 0.000), the value of traditional dance peer group skills (mean 75), and the results of the FGD with partners making innovation program in mental health posyandu. The conclusion is that traditional dance peer group training in preventing movement disorders for ODGJ can be used as health promotion in mentally healthy posyandu.